Why Another Journal? Setting up Environment and Urbanization in 1989. (May 2016) - Satterthwaite, David
This article describes why we set up the journal Environment and Urbanization with a focus on the global south, and on authors from the south. It now has over 10, 000 subscribers, helped by schemes that allow free subscriptions to institutions in the south. The journal has always sought to engage with and publish practitioners as well as academics, and wherever possible, grassroots leaders and politicians. It has had a strong history of documenting local innovation on the part of local governments, NGOs and grassroots organisations and federations, and providing exposure for initiatives that might not otherwise be documented.